A Sensitive Ratiometric Fluorescent Sensor for Zinc(II) with High Selectivity - Junbo Wang; Jiakai Li; Mingda Cao; Yuanyuan Lv (Sensors, 2013)
A new fluorescent Zn2+ chemosensor (P1) based on a functionalized porphyrin was synthesized and characterized. P1 displayed dramatic ratiometric variations in absorption and fluorescent emission spectra upon exposure to Zn2+ due to the formation of a 1:1 Zn2+/P1 complex. The sensor also exhibited high selectivity and sensitivity toward Zn2+ over other common metal ions in the physiological pH range with a detection limit of 1.8 mM. The sensor showed fast response times and excellent reproducibility, thus confirming its potential applicability as a fluorescent sensor for Zn2+ sensing.